Rethinking Education in the Era of Artificial Intelligence (AI): Towards Future Workforce Competitiveness and Business Success - Johnson Lim, Soon Chong; Lee, Ming Foong (Springer, 2024)
In today's increasingly challenging business environment, digital technologies such as industrial internet of things (IIoT), big data analytics, and artificial intelligence (AI) are being adopted by businesses to optimize their operations. The aforementioned digital technologies, as part of the industry revolution 4.0 (IR 4.0), allowed businesses to gain insightful information from their business processes. More recently, the advent of generative AI technology has the potential to reshape the way we work, learn, and live, as well as how business processes can be further enhanced. The rapid advancements in AI have led to transformative changes across various industries, including education. Due to businesses’ growing reliance on digital and AI technologies, it is therefore important to rethink strategies for education and training in order to ensure future workforce competitiveness. This article aims to explore how education can be reimagined to foster future workforce competitiveness for business success in the era of AI. In particular, we highlight the role of technical and vocational education and training (TVET) in preparing future workers for the digital workplace, i.e., reskilling and upskilling initiatives that can help individuals attain the necessary technical skills and competencies to adapt to the changing business environment. We also discuss some of the potential educational strategies that harness the benefits of AI in education, such as an affordable, accessible, and personalized learning process. Lastly, we conclude our work with some indications fo